Sliding/Rolling Phobic Droplets along a Fiber: Measurement of Interfacial Forces - Mead-Hunter, Ryan; Bergen, T.; Becker, Thomas; O'Leary, R.; Kasper, G.; Mullins, Benjamin (American Chemical Society, 2011)
Phobic droplet–fiber systems possess complex geometries, which have made full characterization of such systems difficult. This work has used atomic force microscopy (AFM) to measure droplet–fiber forces for oil droplets on oleophobic fibers over a range of fiber diameters. The work adapted a previous method and a theoretical model developed by the authors for philic droplet–fiber systems. A Bayesian statistical model was also used to account for the influence of surface roughness on the droplet–fiber force. In general, it has been found that the force required to move a liquid droplet along an oleophobic filter fiber will be less than that required to move a droplet along an oleophilic fiber. However, because of the effects of pinning and/or wetting behavior, this difference may be less than would otherwise be expected. Droplets with a greater contact angle ( 110°) were observed to roll along the fiber, whereas droplets with a lesser contact angle (<90°) would slide.